An Evaluation of the Factors that Influence the Job Satisfaction Level Among Personal Financial Consultant of CIMB Bank - Risuki, Abdullah (2011)
Job satisfaction is said to be one of the factors that lead to turnover. High turn-over lead to increase in human resource cost. Thus understanding the job satisfaction level and the factors related to it is important. The objective of the study was to examine the relationship and influence of the four factors; the job and workplace expectation, coaching and guidance, compensation and pay and career growth and opportunity to the job satisfaction level. The research questionnaire based on Job Descriptive Index was used to collect data, and descriptive statistics and Pearson-Correlation analysis was performed. The result shows that there is significant correlation between job and workplace expectation and coaching and guidance to the job satisfaction. On the other hand, the compensation and pay, and career growth and opportunity had no relationship to the job satisfaction level.